Simulation of automated vehicle routing for transportation of goods - Raja Raman Sai Saranya (2017)
Everyday huge amount of money is spent for the transportation of goods within a sector like an airport or a factory. Transportation using Automated Guided Vehicles (AGVs) is a good solution for this problem. The efficiency of routing the vehicles within the network, mainly depends on the routing algorithm that is implemented. Hence this project, which is done in collaboration with the ST Engineering group, Singapore, initially focusses on comparing the existing routing algorithms on the basis of the performance related data like computation time, flexibility of design, generic implementation and the cost involved. Then the algorithm which is identified to be the most suitable one for this dissertation is implemented. Following this, the routing algorithm is integrated with the Changi airport network simulation model (created by Mr. Sarveshwar Arunprasad under Prof. Justin Dauwels using VISSIM) using the Component Object Model (COM) interface. Then the functional correctness of the algorithm in providing the shortest path between any source and destination within the airport network is tested. Finally the routing of the vehicle is simulated in the VISSIM network model.